2003
DOI: 10.1007/s00438-003-0862-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of six novel peroxidase cDNAs from cell cultures of sweetpotato in response to stress

Abstract: Six peroxidase (POD) cDNAs were isolated from suspension cultures of sweetpotato (Ipomoea batatas) by cDNA library screening, and their expression was investigated with a view to understanding the physiological functions of each POD in relation to environmental stress. The gene products encoded by these cDNAs could be divided into two groups, anionic PODs (SWPA4, SWPA5, SWPA6) and basic PODs (SWPB1, SWPB2, SWPB3), on the basis of the predicted pI values of the mature proteins. RT-PCR analysis revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…2. All of the nodes were well supported and were in agreement with previously published phylogenies (Costa et al 2008;Park et al 2003).…”
Section: Phylogenetic Analysissupporting
confidence: 79%
“…2. All of the nodes were well supported and were in agreement with previously published phylogenies (Costa et al 2008;Park et al 2003).…”
Section: Phylogenetic Analysissupporting
confidence: 79%
“…A study in sweet potato showed that the acidic peroxidase gene swpa4 is not expressed in any tissue of the plant during normal growth, but that it is strongly up-regulated upon wounding of leaves, as well as incubation with high concentrations of H 2 O 2 or NaCl (Park et al 2003). This would mean either that the stress factors wounding and some chemicals follow the same pathway leading to peroxidase activation or that swpa4 promoter is involved in several response pathways.…”
Section: Physical Stressesmentioning
confidence: 99%
“…MV is a well-known ROS generating chemical which causes a massive, light-mediated accumulation of superoxide radicals in plant tissues (19). Six POD genes from the suspension cultured cells showed increased expression by MV treatment (13). In the rice plant, certain POD genes expressed in roots were also induced by MV-mediated oxidative stress (20).…”
Section: Differential Expression Of Three Pod Genes In Response To a mentioning
confidence: 99%
“…Two primers (5'-CACTTCCACGACTGCTTCGT-3', 5'-ACGA-AGCAGTCGTGGAAGTG-3') designed from the conserved regions of previously reported POD sequences were employed (8,10,13).…”
Section: Preparation Of Pod Probesmentioning
confidence: 99%
See 1 more Smart Citation